Improving Learning Outcomes of Regional Creative Dance Through the Use of Audio Visual Media on Cognitive and Psychomotor Aspects of Students at Elementary School 2 Pangenjurutengah - Natasha Pangestika (CV. Rayyan Dwi Bharata, 2023)
This study aims to find out (1) To improve the learning outcomes of regional creative dances by using audio-visual media in class IV students at SD Negeri 2 Pangenjurutengah Purworejo. (2) To improve students' cognitive aspects by using audio-visual media in class IV students at SD Negeri 2 Pangenjurutengah Purworejo, and (3) To improve students' psychomotor aspects by using audio-visual media in class IV students at SD Negeri 2 Pangenjurutengah Purworejo. This research is a Classroom Action Research conducted in 2 cycles. The subjects in this study were all fourth grade students at SD Negeri 2 Pangenjurutengah Purworejo, totaling 24 students. Data collection techniques using observation, tests and documentation. The instruments used were observation sheets of cognitive aspects and psychomotor aspects and test items to measure students' learning outcomes. Data analysis using percentages and averages. The results of the study showed that (1) there was an increase in the results of observations on students' cognitive aspects in learning regional creative dance with the application of audio-visual media. The percentage of student completeness from cycle I was 79.17%. The percentage of completeness in cycle II increased after improvements were made to reach 91.67%. This result has reached the specified success indicator, namely 75%. (2) There is an increase in observations on the psychomotor aspects of students in learning dance creations in the entrance area with the application of audio-visual media. The percentage of student completeness from cycle I was 62.50%. The percentage of completeness in the cognitive aspects of students in cycle II increased after improvements in learning were made. reached 95.83%. (3) there is an increase in the average learning outcomes in learning through audio-visual media which has increased, namely in the pre-cycle the total value average is 71.79% and then it increases in cycle I, namely the total value average is 77.42% and then increases again in cycle two, namely the total average value of 81.63%. The increase in completeness in learning outcomes, namely in the pre-cycle mastery of students by 37.50%, then increased in cycle I, namely 75%, and increased again in cycle II, which was 100% of all existing students after there was an improvement in the learning carried out. That way these results have met the specified indicators.